Agile Governance in the Implementation of Integrated Public Service Technology in Bone Regency - Asriadi, ‎; Ibrahim, Muh Akmal (KnE Social Sciences, 2025)
The modernization of public services demands governance that is responsive and adaptive to technological change. Agile governance, with its principles of flexibility, collaboration, and iteration, emerges as a strategic approach to support digital transformation in the public sector. This study aims to explore how the principles of agile governance can be contextually adopted in Bone Regency to accelerate the implementation of technology-based integrated public services. Employing a descriptive qualitative approach through a literature review of 17 national and international journals, this article identifies the core principles of agile governance, local challenges, and case studies of best practices in Indonesia. The findings indicate that adopting agile governance requires changes in bureaucratic culture, improved human resource capacity, and readiness of digital infrastructure. However, significant challenges remain, including hierarchical bureaucratic structures, disparities in digital infrastructure across regions, and low technological literacy among public officials. National case studies, such as the digital transformation of the Ministry of Finance and the Jakarta Investment and One-Stop Integrated Services Agency (DPMPTSP DKI Jakarta), demonstrate that the successful implementation of agile governance heavily depends on organizational readiness, leadership support, and human resource capacity. Contextual implementation in Bone requires adaptive strategies that integrate agile principles with local characteristics to deliver more efficient, inclusive, and accountable public services.